Radial Artery Patency after Trans-radial Cardiac Catheterization in a Bangladeshi Population - Chowdhury, Mashhud Zia; Kabir, CM Shaheen; Nasrin, Sahela; Gomes, Hemanta I; Hakim, Md Enamul; Khan, Saidur Rahman; Haq, M Maksumul (University Heart Journal, 2015)
Background: Transradial cardiac catheterization (TCC) is now preferred method over trans-femoral approach globally including Bangladesh. But the incidence of radial artery occlusion (RAO) after TCC is not infrequent and it ranges from 1-18% in different studies. The aim of our study was to see the incidence of RAO after TCC in a population coming for coronary angiogram and/or coronary intervention and also to evaluate the factors responsible for RAO. Methods: The observational prospective study was performed in all consecutive patients coming for TCC. Pre and three month post-procedural modified Allens test, reverse Barbeau test & Duplex ultrasonography for radial artery diameter (RAD), peak systolic velocity (PSV), end-diastolic velocity (EDV) and resistance index (RI) were measured. Results: 69 patients underwent TCC. Mean age was 54 years, 67% were male, 80% hypertensive, 65% diabetic. Follow-up at third month showed one total RAO (1.45%) and mean RAD of the remaining patients was significantly reduced from 2.2+0.03 mm to 2.1+0.03 mm (p=0.001) but none had any symptom or sign of ischemic hand. PSV, EDV & RI were not significantly altered. Reduction of RAD (to <2.0 mm) were significantly higher in female (p=0.032), but no association was found in presence of diabetes or its duration, hypertension, dyslipidaemia, smoking, peripheral vascular disease. The size & number of catheters used or duration of vascular access sheath kept in the artery did not affect the reduction of RAD.Conclusion: The mean RAD of the study was smaller than other study population, but incidence of RAO is very low. RAD was significantly reduced after procedure without any clinical evidence of ischemia or alteration of flow velocity. Female sex was the only factor found to be associated with reduction of RAD in this study. University Heart Journal Vol. 10, No. 2, July 2014; 66-72